(d2+6d+9)+(d3+6d+9)=(d2+6d+9)+(d3+6d+9

Simple and best practice solution for (d2+6d+9)+(d3+6d+9)=(d2+6d+9)+(d3+6d+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (d2+6d+9)+(d3+6d+9)=(d2+6d+9)+(d3+6d+9 equation:



(d2+6d+9)+(d3+6d+9)=(d2+6d+9)+(d3+6d+9
We move all terms to the left:
(d2+6d+9)+(d3+6d+9)-((d2+6d+9)+(d3+6d+9)=0
We add all the numbers together, and all the variables
(+d^2+6d+9)+(+d^3+6d+9)-((+d^2+6d+9)+(+d^3+6d+9)=0
We get rid of parentheses
d^2+d^3-((+d^2+6d+9)+(+d^3+6d+9)+6d+6d+9+9=0
We do not support edpression: d^3

See similar equations:

| s*4+17=101 | | 4(2l+2)=27 | | –3(2x–4)=2x+5–2(4x–5) | | 2x-7=14x= | | 0,3-0,7x=-0,2 | | 9(x+9)=126 | | 2x-+5=3x+6 | | 5(10-3b)=105-8b+411-4b) | | 1/3x+1=15 | | 3√y=3y | | 14x-8=5x+64 | | (2x+1)=(-5x+3) | | x-70+x+x/2=1280 | | a/3=+8=13 | | -6x=-132+6x | | 8x=2=30 | | 6=p+p+p | | y²-3y-18=0 | | 22x=220 | | 20+(x+15)=90 | | 4x-35=2x-13 | | 3^n=1/3/3 | | 8a-7=5 | | (e+3)×5=25 | | 2x-75=105-x | | 3(2p-1)+2(5p-10)=8= | | 4(3x−2)=2x−5 | | 2x=15+0.50x | | 6(x-2)+1=15 | | 12x+x^2=160 | | 3(2+x)=8x-24 | | 6y-14=40# |

Equations solver categories